Genomic Characterization of the Emerging SARS-CoV-2 Lineage in Two Districts of Campania (Italy) Using Next-Generation Sequencing - Scrima, Marianna; Cossu, Alessia Maria; D'Andrea, Egildo Luca; Bocchetti, Marco; Abruzzese, Ylenia; Iannarone, Clara; Miarelli, Cinzia; Grisolia, Piera; Melisi, Federica; Genua, Lucia; Di Perna, Felice; Maggi, Paolo; et al. (Frontiers in Virology, 2022)
Coronavirus disease 2019 (COVID-19) emerged in December 2019 when the first case was reported in Wuhan, China and turned into a pandemic. We performed Whole Genome Sequencing (WGS) of 101 SARS-CoV-2 strains obtained from individuals from two districts of Campania (Italy) from January to May 2021. The phylogenetic analysis of sequence data identified five types of clades including ten different Pango lineages: 20A (Lineage B.1.258.17, B.1.258.14, B.1.160) (n = 10; 9.9%), 20B (Lineage B.1.1.351, B.1.374) (n = 5; 4.9%), 20E (EU1) (Lineage B.1.177.53, B.1.177.75, B.1.177) (n=5; 4,9%), 20I (Alpha.V1) (B.1.1.7) (n=60; 59.4%), 20 J (Gamma.V3) (Lineage P.1.1) (n = 21; 20.7%). In the early time of epidemics (January and February 2021), B.1.1.7 lineage was in 62% of samples only in Benevento district, while this lineage appears in Avellino later in 64% of samples from March to May. The occurrence of P.1.1 lineage spreading from March to the end of the study and was recorded in all districts with same frequencies of ~21%. The highest genomic distance was observed in lineage P.1.1. Moreover, we identified 219 “know” missense mutations with different frequencies (114 in ORF 1a/1b; 12 in ORF 3a; 29 in S; 5 in M; 29 in N; and 5 each in ORF7a and ORF8). This report suggests the quickly spreading in Campania of new variants of SARS-CoV-2 and the strict surveillance of the occurrence of genetic variants of SARS-CoV-2.